Improved Delay-Dependent Stability Conditions for MIMO Networked Control Systems with Nonlinear Perturbations - Jiuwen Cao (The Scientific World Journal)
This paper provides improved time delay-dependent stability criteria for multi-input and multi-output (MIMO) network control systems (NCSs) with nonlinear perturbations. Without the stability assumption on the neutral operator after the descriptor approach, the new proposed stability theory is less conservative than the existing stability condition. Theoretical proof is given in this paper to demonstrate the effectiveness of the proposed stability condition.